Hypernatremia in exclusively breastfed term neonates - Trivedi, Pinakin; Patel, Ami Himanshu (Indian Journal of Child Health, 2019)
Background: Hypernatremia is known to occur in exclusively breastfed neonates in the first few days of life, and its clinical presentation is usually nonspecific. Early identification and prompt treatment of this condition are necessary to prevent morbidity and mortality. Objective: The objective of the study was to evaluate the clinical features, causative factors, complications, and outcome of hypernatremia in exclusively breastfed term newborns. Materials and Methods: A prospective study of exclusively breastfed healthy term neonates with hypernatremia (serum sodium ?150 mg/dl) was carried out from March 2016 to February 2017. The presenting symptoms, clinical signs, birth and feeding history, and laboratory investigations of the subjects were noted and analyzed. Results: Hypernatremia was noted in 35 (1.6%) of the total term neonates. The condition was more common in babies delivered by cesarean section (34.3%), firstborn neonates (74.3%), and during the summer months (74.3%). Mean age of presentation was 4.06±1.43 days. The most common findings were weight loss ?7 % from the birth weight (74.3%), feeding problems (71.4%), and decreased frequency of urine (60%). Serum sodium levels ranged from 150.5 to 187 mEq/dl. Acute kidney injury was noted in 4 (11.4%) cases. All the patients were discharged, and there was no mortality. Conclusion: Hypernatremia is a common condition in exclusively breastfed neonates. It occurs due to inadequate intake of breast milk by the neonate and is exaggerated in hot environment. Daily weighing of the neonates and monitoring the frequency of urine are important for early detection. Addressing feeding problems early is a simple yet effective measure to prevent this condition.